The intervening impact of mas effectiveness on the relationship between contingent variables and organization performance: a study of Libyan banking and petroleum organizations. / Naser Bashir A. Ghanem - A. Ghanem, Naser Bashir (Institute of Graduate Studies, UiTM, 2017)
This study is undertaken with the purpose of examining the relationship between management accounting system effectiveness (MASE) and organization performance (OP). Specifically the research seeks to figure out what are the benefits derived from MAS that OP could have from what expected to be the main influences in MASE. Moreover, the research concentrates on MASE that resulted from contingent factors, organizational coordination and control requirements (OCCR) and information quality IQ. In particular, examine the effect of MASE arising from OCCR and IQ on OP with regard to individual impact (INIM) in developing countries’ concept, the case of Libya. More specifically, IQ as one of the MAS requirement and OCCR which consist of information interdependence (INFIN), formalization (FO) and information inter-organization (INFORG) are the selected contingent variables, with MASE modelled as intervening mechanism between these contingent variables, and OP. This study also looks for evidences about the effectiveness of suitability of MAS’ information from system users’ perspective (perceptions of MAS’s end users such as CEOs). Previous researchers have realized the contribution of information technology (IT) in improving the individual performance chiefly in terms of productivity and effectiveness (Iivari, 2005a). The study is beneficial and significant because it supports the need to consider individual and environmental factors together. The expected outcome of the research is that MASE that rose from the impact of the contingent variables has a direct positive impact on OP. Also the relation between system effectiveness and performance may effected by INIM…